FOCUS ON TEACHING GRAMMAR IN CONTEXT - Dilafruz Oybekovna Gofurova (New modern researchers: modern proposals and solutions, 2025)
The material presented in this article focuses on teaching grammar as the recent research recognizes the necessity of studying grammar and notes that learning is especially effective if grammar categories are included in meaningful communicative context. The paper is especially useful for secondary school English teachers as it identifies different options for focusing on grammar and integrating it into context, offers examples of learning activities for a specific option. The article also includes the description of the option, its theoretical and empirical basis and an example that illustrates the ways of its implementation in the classroom. The paper highlights the basic principles for teaching grammar, namely E- Factor and A-Factor. E-Factor means Efficiency and, teaching any grammatical category, its components – economy, ease and efficacy – should be kept in mind. A-Factor means Appropriacy and contains a lot of factors, such as learners’ age, their hobbies and interests, learners’ previous level of knowledge, etc. Teachers should consider them all to succeed in grammar presentation. The authors offer multi-vector opportunities for learning grammar to encourage students to learn it understanding its necessity because mastering grammar is the basis of language proficiency.